Penerapan Line of Sight dan Finit State Machine pada Game Platformer “RUN!” - Andi Yusika Rangan; Hendy (Information Technology and Science(ITScience), 2023)
At this time, games have expanded their functions beyond mere entertainment facilities; some are used as a means of learning, business land, and even as a sport by professionals.